Survey research in podiatric medicine: An analysis of the reporting of response rates and non-response bias. (September 2019) - Mulvany, Jessica L.; Hetherington, Vincent J.; VanGeest, Jonathan B.
Highlights: The use of survey research is common practice in podiatry and other health fields. The authors report a secondary analysis of response rate and non-response bias of survey research published in podiatric Journals. The absence of response rates and inconsistent reporting of non-response bias is problematic for studies that contribute best practices. Abstract: Background: Survey research is common practice in podiatry literature and many other health-related fields. An important component of the reporting of survey results is the provision of sufficient information to permit readers to understand the validity and representativeness of the results presented. However, the quality of survey reporting measures in the body of podiatry literature has not been systematically reviewed. Objective: To examine the reporting of response rates and nonresponse bias within survey research articles published in the podiatric literature in order to provide a foundation with regard to the development of appropriate research reporting standards within the profession. Methods: This study reports on a secondary analysis of survey research published in the Journal of the American Podiatric Medical Association, the Foot, and the Journal of Foot and Ankle Research. 98 surveys published from 2000 to 2018 were reviewed and data abstracted regarding the report of response rates and non-response bias. Results: 67 surveys (68.4%) report a response rate while only 36 articles (36.7%) mention non-response bias in any capacity. Conclusions: The findings suggest that there is room for improvement in the quality of reporting response rates and nonresponse in the body of podiatric literature involving survey research. Both nonresponse and response rate should be reported to assess survey quality. This is particularly problematic for studies that contribute to best practices.